Growth of papaya nodal and rooted shoot cultures as affected by ACC, STS, culture vessel size and incubation conditions - Magdalita, P. M. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2003)
Nodal shoot cultures of 'Clone 003', a selected Australian papaya cultivar, were cultured on modified De Fossard medium supplemented with chemicals that either promote ethylene evolution or inhibit action while in culture. Nodal shoot cultures grown in the presence of 1-aminocyclopropane carboxylic acid (ACC, 1.0 mM) resulted in a significant reduction in percent fresh and dry weights, shoot length, leaf area, petiole length and chlorophyll content, but leaf development was significantly increased. In contrast, nodal cultures grown in the presence of silver thiosulphate (STS, 0.5 mM) significantly produced the highest percentage of fresh and dry weights, shoot length, leaf production, leaf area expansion, petiole length and leaf chlorophyll content. Nodal cultures and rooted whole plantlets placed in medium-sized (125 mL) culture vessels had significantly better growth than those cultures placed in small (70 mL) or in large (250 mL) vessels. Cultures grown in medium-sized vessels had higher fresh and dry weights, longer shoots, more leaves and larger leaf area than those cultures placed in smaller or larger vessels. Similarly, values for said growth parameters and for chlorophyll content of the nodal and rooted whole plantlets were higher when they were incubated under high light intensity of 120 μmol m-2s-1 at a prevailing temperature of either 20±1 C or 25±1 C.